PERAN ORANG TUA MENDAMPINGI BELAJAR ANAK DI MASA PANDEMI DI DUKUH NGLAU - Eka Ikromah; Santoso Santoso; Ika Ari Pratiwi (JANACITTA, 2022)
The role of parents is very important because they are people who deal directly with children in the family environment. The purpose of this study was to describe the role of parents and the difficulties of parents in assisting children's learning during the pandemic in Nglau.This study discusses about parents who carry out two roles at once, first being parents and second being teachers at home, providing facilities, motivation, and being children's interlocutors. Difficulties of parents in accompanying children's learning at home are the educational background of parents, the economic level of parents affects the online learning process, especially in terms of facilitating children's online learning, difficulty dividing time between children and work.The results showed that 1) the role of parents in assisting children's learning, namely parents as educators, parents as motivators, parents as role models, parents as friends, parents as supervisors. 2) Difficulties faced by parents in accompanying children's learning are the educational background of the parents, the type of work of the parents, the time available. With this research, parents should be able to guide, provide facilities, provide motivation. spend time accompanying children's learning. Parents' difficulties in knowledge can be overcome by maximizing the explanation of the material in detail from textbooks or learning videos on YouTube.